Scientific notes on Coptosoma variegatum Herrich-Schaeffer, 1838 (Hemiptera: Plataspidae): a potential pest of mango flower in Malaysia - Nurul Huda A.,; Che Salmah M.R.,; Hamdan A.,; Abdul Razak M.N., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The incidence of infestation by a black stink bug Coptosoma variegatum (Hemiptera: Plataspidae) on mango Mangifera indica L. (Anacardiaceae) tree was scientifically reported for the first time in Malaysia. This insect is commonly known as home invader and legume pest. Abundance of this insect was monitored on mango panicles by 15 minutes hourly collection from 0800 h until 1500 h at 4-day interval from the beginning of flowering until all flowers dried up (12-28 February 2013 and 28 January 2014 – 7 March 2014). Five hundred twenty-six individuals collected during the study period with drastic increase observed in second season. However, their infestation on mango flowers was not fully evident therefore was suggested as a potential pest for mango flower in Malaysia solely due to their appearance on mango panicles. Nevertheless, co-occurrence of this sap-sucking insect with other secondary pests may pose a serious economic implication on the productivity of the crop. Thus, more research regarding this insect biology is required so that control requirement can be identified to maximize mango production in Malaysia.